PERCEPTION OF PROFESSIONALS' MENTAL HEALTH PRACTICE ON COMPREHENSIVE CARE IN PRIMARY CARE: AN INTEGRATIVE REVIEW - Silva Junior, Arcanjo de Sousa; Jorge, Maria Salete Bessa; Ferreira, Thiago Silva; Gomes, João Victor de Castro (Seven Editora, 2025)
Objective: to analyze, in the literature, the perception of the Mental Health practice of professionals about comprehensive care in Primary Care. Method: Integrative Review, including LILACS, Medline, SciELO and PubMed databases. The descriptors "Mental Health", "Health Personnel" and "Primary Health Care" were applied. Results: Initially, 12,377 studies were identified and after the selection stages, a sample of 11 articles remained. Through the analysis of the articles through intensive reading, the following categories were formulated: Reality of Mental Health Care in Primary Health Care; Difficulties encountered in carrying out Mental Health care in Primary Care; and Proposed measures to improve Mental Health care in Primary Care.DOI: https://doi.org/10.56238/sevened2025.018-038